UPAYA MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN SEJARAH MENGGUNAKAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBASIS QR CODE PADA KELAS X-11 SMA NEGERI 8 SURABAYA - Dias Alvy Pratama; Agus Suprijono; Defit Ekawati (Institute Agama Islam Al-Qolam Malang, 2023)
This research is aimed to increasing the learning interest of class X-11 students of SMA Negeri 8 Surabaya with a sample of 30 students in history subjects based on the Qr- Code that is Teams Games Tournament (TGT) learning model. This research is a Classroom Action Research (CAR) conducted collaboratively. The design of this study uses data collection techniques based on observation based on questionnaires. Based on the results of the study, it was shown that the application of the Qr Code-based TGT learning model in history subjects could increase the learning interest of X-11 students at SMA Negeri 8 Surabaya. This can be proven through the results of the student learning interest questionnaire from the results of the pre-cycle using the conventional model to get a percentage of learning interest of 38.94%, increasing to 69.43% in cycle I. After modification, in cycle II it shows an increase in learning interest to 83.8%.